La Croix des Marins, Concarneau - Aiken, Walter Chetwood (My University, 2007)
drawing for Salon, after a picture exhibited in the same year
Catalogue of 1896
Keywords: Salon drawings; Art, Irish; Concarneau (France) in art Catalogs; Women's clothing France History; 19th century; Drawing 1860-1900; Children & adults 1890-1900